Single parent role in child psychological development - Nurul Istiani; Athoillah Islamy; Nur Laili Handayani (Institut Agama Islam Negeri (IAIN) Bone-Indonesia, 2020)
This study aims to examine how single parent parenting is applied in fostering children's psychological development. This research is a qualitative research in the form of observation and interview studies. Research subjects (respondents) in this study are single parents due to divorce and death in Krapyak Village, Pekalongan City, Central Java. Meanwhile, the theory used as an analysis knife is the theory of parenting and the theory of psychology of child development. This study concludes that there are three parenting styles performed by single parents in Krapyak Village, Pekalongan City. First, democratic parenting. This parenting pattern has an impact on the child's behavior according to their psychomotor development. Second, authoritarian parenting. This parenting has implications for irritability, cowardice, irritability and emotionality. Third, permissive parenting. This parenting produces behavior in accordance with their own desires and causes the child to be aggressive, rebellious, and lack self-confidence.Penelitian ini bertujuan untuk meneliti bagaimana pengasuhan orang tua tunggal diterapkan dalam membina perkembangan psikologis anak. Penelitian ini merupakan penelitian kualitatif berupa observasi dan studi wawancara. Mata pelajaran penelitian (responden) dalam penelitian ini adalah orang tua tunggal akibat perceraian dan kematian di Kelurahan Krapyak, Kota Pekalongan, Jawa Tengah. Sementara itu, teori yang digunakan sebagai pisau analisis adalah teori pengasuhan dan teori psikologi perkembangan anak. Penelitian ini menyimpulkan ada tiga gaya pengasuhan yang dilakukan oleh orang tua tunggal di Kelurahan Krapyak, Kota Pekalongan. Pertama, pengasuhan demokrasi. Pola pengasuhan ini berdampak pada perilaku anak sesuai dengan perkembangan psikomotor mereka. Kedua, pengasuhan otoriter. Pengasuhan ini memiliki implikasi untuk lekas marah, pengecut, lekas marah dan emosionalitas. Ketiga, pengasuhan permisif. Pengasuhan ini menghasilkan perilaku sesuai dengan keinginan mereka sendiri dan menyebabkan anak menjadi agresif, memberontak, dan kurang percaya diri.